Integrating Music Activities into Social Studies Learning for Grade Students IV SD Pedagogia as a Deep Learning Approach to Improve Conceptual Understanding - Muflikhul Khaq; Raudya Setya Wismoko Putri; Lina Ambarwati; Mita Saputri (Journal of Innovative and Creativity, 2025)
This study aims to explore the integration of music activities in Social Studies (IPS) learning as a form of implementing deep learning-based pedagogy to improve conceptual understanding of fourth grade elementary school students. Using a qualitative approach with a case study design, data were collected through participatory observation, in-depth interviews with teachers and students, and analysis of learning documents. The results of the study indicate that the integration of music in IPS learning through historical-themed songs, rhythms for memorizing facts, and other creative activities can increase student engagement, facilitate emotional connections with the material, and deepen conceptual understanding of topics such as cultural diversity, the history of the nation's struggle, and social structures. This pedagogical approach also encourages collaboration, creativity, and reflection, which are the main characteristics of deep learning. These findings indicate that music can be an effective means of building a more meaningful and contextual learning experience in the eyes of elementary school students.